China’s Creative Industries - Yanzhina Z. Gomboeva (Гуманитарный вектор)
The article presents the results of describing the general state of China’s creative industries. The paper describes the main types of economic activities included in the list of cultural industries of China as objects of multi-level administration, reveals the prospects for the development of certain types of economic activities, especially important for the development of culture and the creative economy of the country.The content of the article and the results of the study are of practical importance. The exchange of experience and knowledge in the field of creative industries development between our countries can significantly enrich existing Russian domestic practices and ultimately lead to a synergistic effect. We prove that the development of China’s creative sector is considered as a continuation of China’s global implementation of the national strategy “One Belt, One Road”, as a tool for implementing the policy of “soft power” and this experience is the weakest force that is needed in connection with modern world events.The problem of the prospects for the development of China’s creative industries in the global market is revealed. Creative industries on digital platforms face the need to enter new markets in the global creative services industry. Traditional state-subsidized cultural heritage has shown its weak competitiveness compared to digital content. Digital culture is commercialized, customer-centric and focuses on the needs of individuals and specific communities, it has had a strong positive impact on the image and economy of modern China.The Chinese government’s action plan for the implementation of the Internet Plus program aims to integrate mobile Internet, cloud computing, big data and Internet of Sales with industrial sectors to promote economic restructuring, improve service for people’s lives, including government functions. This plan is at an early stage of fine-tuning integration to the principles of the ecosystem, as a set of open and customizable platforms. The developers of the program are refining the functions to the possibility of application not only in production, but also in finance, trade, transport, healthcare and education.